Outlook for new CAR-based therapies with a focus on CAR-NK cells: what lies beyond CAR-engineered T cells in the race against cancer - Daher, May (Cancer Discov, 2020)
Chimeric antigen receptor (CAR) engineering of T cells has revolutionized the field of cellular therapy for the treatment of cancer. Despite this success, autologous CAR-T cells have recognized limitations that have led to the investigation of other immune effector cells as candidates for CAR modification. Recently, natural killer (NK) cells have emerged as safe and effective platforms for CAR engineering. In this article, we review the advantages, challenges and preclinical and clinical research advances in CAR-NK cell engineering for cancer immunotherapy. We also briefly consider the feasibility and potential benefits of applying other immune effector cells as vehicles for CAR expression.